participatory democracy in action : International profilesof community development . - Chekki, Dan A. (New Delhi, 1979)
This book is a sequel to our Community Development: Theory and Method of Planned Change, which focussed its attention mainly on conceptual-theoretical, and methodological aspects of community development. This second volume, however, aims to provide cross-national profiles, case studies, and commentaries on demo cratic citizen participation in various types and contexts of community development processes.
Keywords: Community development